Implementasi Corporate Social Responsibility (CSR) Artha Graha Peduli dalam Perspektif Al-Qur'an dan Hadis - Eka Destarada Sesunan; Abdul Aziz; Anton Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of social care values ​​in the Corporate Social Responsibility (CSR) program of Artha Graha Peduli (AGP) which consists of five main pillars, namely environmental conservation, disaster management, social community, community empowerment, and law and justice, from the perspective of the Qur'an and hadith. This study uses a descriptive qualitative method with a normative and conceptual approach. The data sources used include primary data in the form of the Qur'an and hadith, as well as secondary data from reputable scientific journals (Scopus and Sinta), books, and reports related to the AGP program. Data collection techniques are carried out through literature studies and documentation, while data analysis uses a descriptive and thematic approach to relevant verses of the Qur'an and hadith. The results of the study indicate that the implementation of the five pillars of AGP has a high level of conformity with Islamic values, particularly within the framework of maqashid sharia which includes protection of life (hifz an-nafs), wealth (hifz al-mal), reason (hifz al-‘aql), descendants (hifz an-nasl), and religion (hifz ad-din). The AGP program also reflects the main values ​​in Islam such as ta’awun (mutual assistance), ihsan (goodness), ukhuwah (brotherhood), and justice (‘adl). In addition, the CSR practices carried out by AGP are not only philanthropic, but have developed towards a more holistic approach through the concept of Corporate Social and Safety Responsibility (CSSR) which integrates social, ethical, safety, and sustainability aspects. This study also found that the implementation of AGP CSR can be categorized as Islamic Corporate Social Responsibility (ICSR), namely the integration of sharia principles and modern CSR practices oriented towards the benefit (maslahah) and welfare of society in a sustainable manner. Thus, AGP represents a concrete implementation of Islamic social responsibility values ​​in a modern context, encompassing not only social dimensions but also spiritual, ethical, and sustainable ones. This study concludes that integrating Islamic values ​​into CSR practices can strengthen the effectiveness of social programs and enhance a company's social legitimacy. Therefore, strengthening the implementation of Islamic-based CSR through a maqasid sharia approach and collaboration with religious and social institutions is necessary to create a broader and more sustainable impact.